Bahasa Inggris Bahasa Inggris - Lilik Masykuroh Hadah; Sayyidatul Maghfiroh; Naza Zulmia Humaira; Wahyu Nur Akhada (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - This research aims to figure out the relationship between those two productive skills focusing on four aforementioned crucial aspects in language learning. Design/methodology/approach - This study used a cross-sectional quantitative method with 32 English Education Department students in the 6th semester at Universitas Islam Negeri Sunan Ampel Surabaya who have already been experienced in spoken and written class to be the participants. In terms of gaining the data, It used pictured cued interviews and answer the open-ended question related to the best way in finding a job and give their opinion within 30 minutes. Both of the tests were adapted from the TOEIC sample test from the Educational Testing Service (ETS). Finally, use SPSS 2.2 for the data analysis. Findings - The result shows that the organization gains the highest rate or simply as the most related part among the other language learning. Furthermore, the correlation between the two productive skills also shows a moderate correlation. Originality/value - It simply said that speaking and writing show an insignificant correlation with the organization as the most related part of language learning. Paper type – Research paper